2009
DOI: 10.1159/000241096
|View full text |Cite
|
Sign up to set email alerts
|

Change in Cochlear Response in an Animal Model of Otitis Media with Effusion

Abstract: Our previous studies confirm that middle ear mobility is reduced in the presence of otitis media with effusion (OME). Variations in middle ear function may result in changes in cochlear response in OME ears. With the long-term goal of evaluating cochlear function in OME ears, the aim of this study was to measure the displacement of the basilar membrane (BM) in guinea pig ears with OME. Vibrations of the BM at the apex and basal turn were measured in an in vitro preparation extracted 3 and 14 days after injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
4
7
1
Order By: Relevance
“…The AOM group includes eight animals and the control group includes four animals. The AOM model was created by injection of Streptococcus pneumoniae type 3 (Sp3) (ATTC 6303, Manassas, VA, USA) suspension into the left middle ear (N08) following the procedure reported by Dai et al (2009). S. pneumoniae is one of the most common bacteria found in AOM effusion (Gould and Matz 2010).…”
Section: Animal Preparationmentioning
confidence: 99%
“…The AOM group includes eight animals and the control group includes four animals. The AOM model was created by injection of Streptococcus pneumoniae type 3 (Sp3) (ATTC 6303, Manassas, VA, USA) suspension into the left middle ear (N08) following the procedure reported by Dai et al (2009). S. pneumoniae is one of the most common bacteria found in AOM effusion (Gould and Matz 2010).…”
Section: Animal Preparationmentioning
confidence: 99%
“…Similarly, measurements of cochlear microphonic in chinchillas revealed that thresholds increased by 20–40 dB across the range of frequencies tested, umbo velocities decreased by 15–35 dB, and once again the increases in threshold were directly proportional to the amount of fluid in the middle ear and not affected by the viscosity of the fluid (12,13). Similar experiments in guinea pigs measuring basilar membrane motion with LDV revealed a reduction of 25 dB at all tested frequencies (14). In sum, previous studies have described conductive losses associated with middle ear effusion, but with conflicting reports of the frequency-dependence and magnitude of the induced conductive loss.…”
Section: Introductionmentioning
confidence: 57%
“…In guinea pigs, otitis media produced (a) small changes in ossicular transmission 3 and 7 days post-inoculation but a significant decrease between 1 and 12 kHz at 14 days post-inoculation (Dai and Gan, 2008) or (b) a reduction in ossicular transmission of up to 16 dB at 400 Hz and 10 dB at 11 kHz 3 days post-inoculation and an insignificant reduction between 200 and 600 Hz and up to a 13-dB reduction at 14 kHz (Dai and Gan, 2010) 7 . Once the ME static pressure was released and ME fluid was drained, (c) umbo displacements in guinea pig and chinchilla were 5–8 dB lower below 1 kHz than in control ears (Guan and Gan, 2013; Guan et al, 2014), but (d) residual reductions of umbo and incus displacements were similar (Guan and Gan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“… 7 Ossicular transmission was evaluated by the ratio of umbo displacement to round window displacement (Dai and Gan, 2008) or by the ratio of basilar membrane displacement at the cochlear apex or basal turn, respectively, to umbo displacement (Dai and Gan, 2010). …”
mentioning
confidence: 99%